Critical commentary on the judgment of the Appellate Court in Lublin dated 23 June 2022 (case no. I ACa 184/22) - Łebek, Piotr (The Opole Studies in Administration and Law, 2025)
The judgment commented on contributes to the ongoing scholarly discourse regarding the necessity of developing coherent and transparent standards for assessing allegations of arbitrator bias within sports arbitration proceedings. In addressing this multifaceted issue, two central questions emerge: firstly, whether any concern raised regarding an arbitrator’s potential lack of impartiality should automatically constitute sufficient grounds to set aside an arbitral award, and secondly, to what extent the internationally recognized IBA Guidelines on Conflicts of Interest can be effectively employed to assess arbitrators’ independence in sports-related disputes. It is argued that the mere assertion of partiality does not justify overturning a rendered arbitration decision. It is rather a comprehensive, case-specific analysis of the arbitrator’s conduct within the broader factual and procedural context that is imperative. In this regard, the IBA Guidelines assume particular significance, as they offer a structured, objective, and widely accepted methodological framework for evaluating potential conflicts of interest. Achieving an equilibrium between the procedural safeguards afforded to parties and the principle of arbitral award finality is paramount. Enhancing transparency and expanding disclosure obligations bolster confidence in arbitration,thereby facilitating the expeditious and equitable resolution of sports-related disputes.